The effect of TiO2 on the structure of Na2O-CaO-SiO2 glasses and its implications for thermal and mechanical properties - Limbach, Rene; Karlsson, Stefan; Scannell, Garth; Mathew, Renny; Eden, Mattias; Wondraczek, Lothar (Journal of Non-Crystalline Solids, 2017)
Titania represents an important compound for property modifications in the widespread family of soda lime silicate glasses. In particular, such titania-containing glasses offer interesting optical and mechanical properties, for example, for substituting lead-bearing consumer glasses. Here, we provide a systematic study of the effect of TiO2 on the structural, thermal, and mechanical properties for three series of quaternary Na2O–CaO–TiO2–SiO2 glasses with TiO2 concentrations up to 12 mol% and variable Na2O, CaO, and SiO2 contents. Structural analyses by Raman and magic-angle spinning 29Si NMR spectroscopy reveal the presence of predominantly four-fold coordinated Ti[4] atoms in glasses of low and moderate TiO2 concentrations, where Si–O–Si bonds are replaced by Si–O–Ti[4] bonds that form a network of interconnected TiO4 and SiO4 tetrahedra, with a majority of the non-bridging oxygen ions likely being located at the SiO4 tetrahedra. At higher TiO2 contents, TiO5 polyhedra are also formed. Incorporation of TiO2 strongly affects the titanosilicate network connectivity, especially when its addition is accompanied by a decrease of the CaO content. However, except for the thermal expansion coefficient, these silicate-network modifications seem to have no impact on the thermal and mechanical stability. Instead, the compositional dependence of the thermal and mechanical properties on the TiO2 content stems from its effect on the network energy and packing efficiency.
CRIS-Team Scopus Importer:2023-04-20